2008
DOI: 10.1038/eye.2008.230
|View full text |Cite|
|
Sign up to set email alerts
|

Vitreous levels of erythropoietin in patients with macular oedema secondary to retinal vein occlusions: a comparative study with diabetic macular oedema

Abstract: Objective In a recent study, we found high levels of erythropoietin (EPO) in patients with diabetic macular oedema (DME), suggesting a role of EPO in the pathogenesis of this condition. To investigate a possible relationship between EPO and other diseases causing macular oedema, we determined vitreous levels of this peptide in patients with macular oedema secondary to retinal vein occlusion (RVO) and compared them with levels in patients with DME and control patients. Methods Vitreous and serum samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, intravitreal levels of Epo have been found at a similar range in PDR to that in DME (a condition in which hypoxia is not a predominant event) [52] . In addition, intravitreal Epo levels are not elevated in non-diabetic patients with macular edema secondary to retinal vein occlusion [60] . Finally, a higher expression of Epo has been detected in the retinas of diabetic donors at early stages of DR compared to non-diabetic donors and this overexpression is unrelated to mRNA expression of hypoxic inducible factors (HIF-1α and HIF-1β) [53] .…”
Section: Sstmentioning
confidence: 99%
“…However, intravitreal levels of Epo have been found at a similar range in PDR to that in DME (a condition in which hypoxia is not a predominant event) [52] . In addition, intravitreal Epo levels are not elevated in non-diabetic patients with macular edema secondary to retinal vein occlusion [60] . Finally, a higher expression of Epo has been detected in the retinas of diabetic donors at early stages of DR compared to non-diabetic donors and this overexpression is unrelated to mRNA expression of hypoxic inducible factors (HIF-1α and HIF-1β) [53] .…”
Section: Sstmentioning
confidence: 99%
“…They interpreted the ischaemia-induced, elevated EPO level as a possible endogenous neuroprotective reaction. Garci-Arumi et al 22 found a mean concentration of 25 (range 10 to 75) mU/ml in patients with epiretinal membranes and macular holes and 430 (range 41 to 3000) mU/ml in diabetic macular oedema. Finally, Asensio-Sanchez et al 23 measured 25 (range 5–201) mU/ml in non-ischaemic patients compared with 512 (120 to 880) mU/ml in cases of proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 96%
“…Its expression, like VEGF expression, is ischemia induced. Its levels are increased in the vitreous of patients with proliferative diabetic retinopathy and diabetic macular edema [84]. However, its actions on angiogenic vascular proliferation seem to be independent of VEGF activity [83,85].…”
Section: Erythropoietinmentioning
confidence: 99%